2022
DOI: 10.1088/1742-6596/2369/1/012064
|View full text |Cite
|
Sign up to set email alerts
|

Identification of vulnerable node groups in wind power grids based on K-order structure entropy

Abstract: Power outage accidents are caused by chain failures caused by the failure of vulnerable components affecting a certain range of components. Identifying the spread impact range of vulnerable nodes can effectively improve the system’s vulnerability. Large-scale wind power grids connection increases the complexity of the power systems and brings new challenges to the identification and simulation of vulnerable nodes. In this paper, a method for identification of vulnerable node groups in wind power grids is propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…A literature review was conducted to analyse the current state of the literature on managing cybersecurity risks in emerging technologies. The results showed that emerging technologies can enhance cybersecurity and resilience for organisations, but there are also challenges that organisations may face when implementing these technologies (Li et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review was conducted to analyse the current state of the literature on managing cybersecurity risks in emerging technologies. The results showed that emerging technologies can enhance cybersecurity and resilience for organisations, but there are also challenges that organisations may face when implementing these technologies (Li et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous approaches and techniques have been suggested to enhance the security and robustness of power grid networks. The identification and modelling of nodes within these grids have become vital in order to strengthen system resilience and reduce risks (Li et al, 2022). Measures like access control policies grained dynamic access control methods, and security assessment technologies have been explored to protect power grid systems from access and cyber threats (Li et al, 2023;Qiu et al, 2022).…”
Section: Technical Challengesmentioning
confidence: 99%
“…The results show that the more homogeneous the structure, the higher the reliability and high robustness of the grid and the lower the vulnerability. In order to integrate the non-uniformity of the system structure and state, [47][48] proposed the use of entropy theory to improve the metrics, integrating the equilibrium of the system and the fluctuation of the tidal currents. To solve the lack of comprehensive evaluation method, [49] used VIKOR comprehensive evaluation method to get the node importance ranking.…”
Section: Introductorymentioning
confidence: 99%